PENGARUH KESEMPATAN PERTUMBUHAN DAN INVESTASI JANGKA PANJANG TERHADAP LEVERAGE DAN FUTURE EARNINGS RESPONSE COEFFICIENT - Etty Murwaningsari (Universitas Trisakti, 2013)
The objectives of this research are to analyze direct effects of growth opportunity and long term investment towards future earnings response coefficient, as well as their indirect effects towards future earnings response coefficient through leverage as intervening variable. This research used secondary data from manufacturing companies listed in Indonesia Stock Exchange (IDX) between 2002-2011. Number of samplesused in this research are 111 companies. Method used in this researchis Structure Equation Model (SEM) processed using AMOS 6. Results from this research demonstrated that growth opportunityhas positive and significant effect whilst longterm investment andleverage have negative and significanteffects towardsfuture earnings response coefficient. On the other hand, growth opportunity and long term investment have positive significant towards leverage. Further testing proved that indirect effect is very weak. Control variableswhich have positive significant effect are fixed assets and institutional possession towards leverage and future earnings response coefficient. For company size variables and audit quality were proven to have no effect towards leverage and future earnings response coefficient.Keywords: Growth Opportunity, Long Term Investment,Leverage, Future Earnings Response Coefficient (FERC)